2019
DOI: 10.1111/ajd.13100
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase‐4 inhibitors and bullous pemphigoid: A systematic review and adjusted meta‐analysis

Abstract: Background/Objective There have been a number of case reports and small clinical series reporting the potential association between dipeptidyl peptidase‐4 inhibitors (DPPIs) for diabetes and the onset of bullous pemphigoid (BP). The aim of this study was to assess the association between DPPI use and BP, and whether this varied according to DPPI type. Methods We performed a systematic review and meta‐analysis according to PRISMA guidelines. We identified five studies with cases and controls. We performed unadj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 31 publications
4
39
1
2
Order By: Relevance
“…The recent meta‐analysis study reported that the association between DPP‐4 inhibitors and BP was significant in both males and females (OR, 2.35; P = 0.0005; and OR, 1.88; P = 0.02; respectively) . Subgroup analysis conducted in our study also showed that the higher risks of BP in DPP‐4 inhibitor users were found in both male and female patients with DM (aHR, 2.198; P = 0.018; and aHR, 2.676; P = 0.001; respectively).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The recent meta‐analysis study reported that the association between DPP‐4 inhibitors and BP was significant in both males and females (OR, 2.35; P = 0.0005; and OR, 1.88; P = 0.02; respectively) . Subgroup analysis conducted in our study also showed that the higher risks of BP in DPP‐4 inhibitor users were found in both male and female patients with DM (aHR, 2.198; P = 0.018; and aHR, 2.676; P = 0.001; respectively).…”
Section: Discussionsupporting
confidence: 71%
“…A recent meta‐analysis study of five case–control studies showed a significant association between DPP‐4 inhibitors and BP (OR, 2.13; 95% CI, 1.59–2.86; P < 0.00001) . The study also reported a strong association between vildagliptin and BP (OR, 5.08; 95% CI, 1.70–15.19; P = 0.004), followed by linagliptin (OR, 2.87; 95% CI, 1.06–7.79; P = 0.04), but not in sitagliptin (OR, 1.29; 95% CI, 0.79–2.08; P = 0.31).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Emerging evidence has established a relationship between DPP4i and the development of BP (OR, 2.13-97.69; Table S1). [42][43][44][45][46][47][48][49][50][51][52][53][54][55] Vildagliptin is the leading DPP4i to confer increased risk of BP The extracellular domain comprises dipeptidyl peptidase activity which selectively removes the X-proline or X-alanine dipeptide residues in the penultimate position from the NH 2 -terminus of polypeptide substrates. The extracellular catalytic domain of DPP4 serves as a binding site for substrates and inhibitors.…”
Section: Bullous Pemphi G Oid and Mucous Memb R Ane Pemphigoidmentioning
confidence: 99%
“…Adapted from Ohnuma et al 2 and anagliptin (111.07), which are less frequently used, 43,45,56 and omarigliptin (OR, 557.20), teneligliptin (OR, 29.23-161.9), and trelagliptin (OR, 178.18), which are available in fewer countries, such as Japan, Argentina, Korea, and India. 42,45,57 Whilst individual studies found no significant risk associated with sitagliptin use, a recent meta-analysis of randomized controlled trials involving sitagliptin, saxagliptin and linagliptin identified a significant association (OR, 7.38) 12,46,47 In addition to BP, DPP4i appear to predispose towards mucous membrane pemphigoid (MMP) development. In a study examining gliptin accountability in a cohort of 313 MMP patients, 17 of 24 gliptin-treated diabetic MMP patients were considered gliptin-induced MMP due to onset within <12 weeks.…”
Section: Bullous Pemphi G Oid and Mucous Memb R Ane Pemphigoidmentioning
confidence: 99%